ECOLOGY OF HOUSEHOLD WASTE UTILIZATION AND RECYCLING: MODERN APPROACHES AND PRACTICES IN UZBEKISTAN - Gulnoza Gulmuratovna Turaeva (Modern American Journals, 2025)
This article explores the ecological dimensions of household waste utilization and recycling in the context of Uzbekistan. With the growing volume of municipal solid waste and its environmental impact, the need for sustainable waste management strategies has become increasingly urgent. The study reviews modern approaches, including source separation, composting, waste-to-energy technologies, and circular economy models, while assessing their applicability within Uzbekistan’s current infrastructural and policy frameworks. Special attention is paid to the ecological consequences of improper waste disposal and the role of community participation in improving waste management systems. The article also highlights national initiatives and international cooperation efforts aimed at promoting recycling culture and ecological awareness. By analyzing challenges and offering evidence-based recommendations, the paper contributes to the academic discourse on sustainable environmental practices in developing countries.
Keywords: Household waste, ecology, recycling, waste management, sustainable development, Uzbekistan, environmental policy, circular economy, green technologies, public awareness